Comparative analysis of verb categories in the languages of the Oghuz ethnic group - Balakhozhaуeva, А.Б.; Kuanyshbayev, Е.А. (Bulletin of L.N. Gumilyov Eurasian National University. PHILOLOGY Series, 2023)
The article examines the category of tenses in Turkish, Azerbaijan and Turkmen languages, which are part of the Oghuz group of Turkic languages. The article aims to conduct a comparative analysis of three languages to define their commonalities and differences. To achieve this goal, it is necessary to identify functional, terminological, and structural features of the issued languages as research objectives. In order to accomplish the established goal and objectives of the study, synchronous comparative, comparative typological and structural research methods were used. During the discussion of the study, the systems of categories of tenses were described, their structural, syntactic, morphological and semantic features were identified and compared. As a result of the study Turkish, Azerbaijan and Turkmen languages have demonstrated some common linguistic features that are general for Turkic languages, as well as individual features and differences regarding the tense category. There are certain differences in the natural structure of these three languages due to the influence of other language groups and cultures. These differences are mainly related to the structural aspects of the categories of the times of the three languages of the Oghuz group. In Turkish, the system of tenses categories is formed on the basis of suffixes. Although the Azeri language is very similar to Turkish, it is limited to the traditional system of three tenses, in which suffixes have no structural meaning. Despite the fact that Turkmen differs from Turkic and Azerbaijani languages due to some features, the tense category in Turkmen are structurally similar to Azerbaijani language. The tense category of the Turkish language is descriptive, while in the Azerbaijani and Turkmen languages they are formed using a prescriptive method.